2020
DOI: 10.1109/access.2020.3005733
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Physician’s Experience With Conversational Interfaces During Occupational Health Consultation

Abstract: This paper presents an exploratory study on using conversational interfaces (CIs) to support physicians in conducting occupational health consultations. The CI was achieved through a web-based information dashboard with a chatbot assistant for providing real-time suggestions through text messages. Two system designs were developed: the first using a proactive chatbot, the second using an on-demand type of interaction. The effectiveness of the proposed CI and the two types of chatbot designs were investigated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…State-of-the-art AI and Natural Language Processing (NLP)-boosted conversational assistants can automatically sustain dialogues with end users [ 9 , 10 , 11 ]. Nowadays, chatbots are commonly applied to management [ 12 , 13 , 14 ], education [ 15 , 16 , 17 ] and healthcare [ 18 , 19 , 20 ]. It has been demonstrated that they perform better when designed on purpose for specific domains and user groups, and when their utterances are short and accurate within those domains.…”
Section: Related Workmentioning
confidence: 99%
“…State-of-the-art AI and Natural Language Processing (NLP)-boosted conversational assistants can automatically sustain dialogues with end users [ 9 , 10 , 11 ]. Nowadays, chatbots are commonly applied to management [ 12 , 13 , 14 ], education [ 15 , 16 , 17 ] and healthcare [ 18 , 19 , 20 ]. It has been demonstrated that they perform better when designed on purpose for specific domains and user groups, and when their utterances are short and accurate within those domains.…”
Section: Related Workmentioning
confidence: 99%
“…Recent AI advances have enabled chatbots to automatically generate responses to user requests [15]. As a result, they are now widely used in domains such as business [16], education [17], [18] and healthcare [19], [20]. However, they are still very far from mimicking human intelligence [9].…”
Section: Introductionmentioning
confidence: 99%